Theoretical analysis of the main definitions of the social-humanities training studies of the masters of natural specialties under the distance learning conditions - Попенко, Н. В. (Scientific notes of the pedagogical department, 2019)
The purpose of the ar cle is the theore cal analysis of the conceptual-categorical apparatus of the study of social and humanitarian training of Masters of Natural Sciences under the condi ons of distance learning. The research uses theore cal methods, among them: theore cal and system analysis of regulatory, scien fic and educa onal and educa onal-methodical literature on the research problem; systema za on of theore cal developments and defini on of the conceptual-categorical apparatus; generaliza on of informa on. The analysis allowed to dis nguish three groups of the main defini ons of research: 1) prepara on of Masters of Natural Science, 2) social and humanitarian training 3) distance learning technology. The arguments presented in this ar cle have allowed to determine that the Master of Natural Sciences is a professional who has in-depth qualita ve fundamental and special training and is able to solve industrial, scien fic and technological tasks and problems in the field of natural sciences, to carry out an eﬀec ve professional produc on and scien fic-technological ac vity in this area. It was found out that the important direc on of the educa onal and professional development of the future specialist in the field of natural sciences in higher educa onal ins tu on is the socio-humanitarian component of its training. The concept of social and humanitarian competence is defined in accordance with the structure which includes such aspects as cogni ve, ac vity, value-seman c. It has been determined that modern requirements to the higher educa onal establishment graduates make it necessary to find new approaches to the process of professional training of Masters, in par cular, the introduc on of the distance learning technologies. On the basis of theore cal analysis of scien fic and pedagogical sources, the content of the main concepts of the study of social and humanitarian training of Masters of Natural Sciences under the condi ons of distance learning has been characterized and the theore cal substan a on of their essen al characteris cs has been made. The prospects of further explora on in this direc on will lie in the study of the current state of social and humanitarian training of Masters of Natural Sciences in the higher educa onal establishments and the introduc on of elements of distance learning in the educa onal process.